2009
DOI: 10.1017/s0376892909990208
|View full text |Cite
|
Sign up to set email alerts
|

Rapid primary productivity changes in one of the last coastal rainforests: the case of Kahua, Solomon Islands

Abstract: SUMMARYThe growth of human populations has many direct and indirect impacts on tropical forest ecosystems both locally and globally. This is particularly true in the Solomon Islands, where coastal rainforest cover still remains, but where climate change and a growing human population is putting increasing pressure on ecosystems. This study assessed recent primary productivity changes in the Kahua region (Makira, Solomon Islands) using remote sensing data (normalized difference vegetation index, NDVI). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…Saleska et al (2007) demonstrated that reduced rainfall resulted in satellite-based primary productivity estimates that are higher than observed values during the wet season in a South American wet tropical region. Garonna et al (2009) highlighted the same pattern: with clouds being more likely to bias NDVI estimates in wet months than in dry months, and with more light reaching the canopy during the dry season, higher NDVI values were reported during the dry season in the Solomon Islands.…”
mentioning
confidence: 75%
“…Saleska et al (2007) demonstrated that reduced rainfall resulted in satellite-based primary productivity estimates that are higher than observed values during the wet season in a South American wet tropical region. Garonna et al (2009) highlighted the same pattern: with clouds being more likely to bias NDVI estimates in wet months than in dry months, and with more light reaching the canopy during the dry season, higher NDVI values were reported during the dry season in the Solomon Islands.…”
mentioning
confidence: 75%
“…The Kahua region is one of the only areas on the island not to have any commercial logging licenses (past or present; Pauku 2009), and because logging companies are interested mainly in flat, lowland areas, the steep terrain of the Kahua region could be considered a relatively safe sanctuary for biodiversity. However, decreases in primary productivity have been detected in Kahua, suggesting environmental change at a landscape scale (Garonna et al 2009). One of the most noticeable changes within the Kahua region is the proliferation of cacao plantations (Davies et al 2015).…”
Section: Study Areamentioning
confidence: 99%
“…1). Raw NDVI data were then smoothed (Garonna et al, 2009), and average values were obtained for each population and season.…”
Section: Primary Productivitymentioning
confidence: 99%